Can You Hear Africa Roar? Story Time and the Digital Publishing Innovations of Ivor Hartmann and Emmanuel Sigauke. - Jaji, Tsitsi (Journal of Commonwealth & Postcolonial Studies)
The article offers information on the views of Ivor Hartmann and Emmanuel Sigauke regarding the innovations in stories and the digital publishing. It mentions that that they focus on their electronic publishing work and conditions of publishing that can frustrate writers of Africa. It also states the expressions of slangs for the current situations of life.